Uji Aktivitas Penghambatan Enzim α-Glukosidase serta Uji Mutu Ekstrak Etanol Batang Brotowali (Tinospora crispa (L.) Miers.) - YESI DESMIATY; RISMA MARISI TAMBUNAN; KARTININGSIH KARTININGSIH; LOLA DYAH PITHALOKA (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
In attempt to develop Indonesian traditional medicine (Jamu) to become standardize herbal, it is need to examine the extract that can guarantee its efficacy, quality and safety. Brotowali stem (Tinospora crispa (L.) Miers.) known has antidiabetic effect and no toxic activity. In this research, the quality and α-glukosidase inhibitor activity of ethanolic extract of brotowali stem has been determined. In the quality test were determined specific parameters (identity, organoleptic, extractable matter), non specific parameters (loss on drying, water content, total ash content, solvent residue, heavy metal, and microbial contamination), quantification of markers content (total flavonoid content with spectrophotometric UV-Vis and assay of apigenin content with densitometric method). The research showed that the extract was fulfiled the requirement, total flavonoid content was 0.52% and apigenin content was 0.03635%. The result of α-glukosidase inhibitor activity test gave IC50 of 237.26 ppm.